On Contra-$(τ_1,τ_2)p$-continuity and Almost Contra-$(τ_1,τ_2)p$-continuity for Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents four new classes of multifunctions called upper contra-$(τ_1,τ_2)p$-continuous multifunctions, lower contra-$(τ_1,τ_2)p$-continuous multifunctions, upper almost contra-$(τ_1,τ_2)p$-continuous multifunctions and lower almost contra-$(τ_1,τ_2)p$-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper contra-$(τ_1,τ_2)p$-continuous multifunctions, lower contra-$(τ_1,τ_2)p$-continuous multifunctions, upper almost contra-$(τ_1,τ_2)p$-continuous multifunctions and lower almost contra-$(τ_1,τ_2)p$-continuous multifunctions are established.
Keywords: upper contra-$(τ_1,τ_2)p$-continuous multifunction; lower contra-$(τ_1,τ_2)p$-continuous multifunction; upper almost contra-$(τ_1,τ_2)p$-continuous multifunction; lower almost contra-$(τ_1,τ_2)p$-continuous multifunction